Attitudes and beliefs regarding umbilical cord clamping among midwives, obstetricians, and neonatologists in Sweden: A national cross-sectional survey - Maria Wilander; Katarina Ekelöf; Elisabeth Saether; Denice Berglund; Katarina Patriksson; Jenny Svedenkrans; Heike Rabe; Ola Andersson; Li Thies-Lagergren (PLoS ONE, 2025)
Objective The study aimed to explore attitudes and beliefs among midwives, obstetricians, and neonatologists regarding umbilical cord clamping practices, including scenarios involving neonatal compromise. The study was conducted in the context of exploring the potential for implementing intact cord resuscitation. Study design A national cross-sectional survey was administered electronically, using an adaptation of the previously used questionnaire developed by Jelin et al. The survey was conducted among midwives, nursing staff, obstetricians, and pediatricians/neonatologists from September 2022 to August 2023. Results were analyzed and reported using descriptive and inferential statistics. Result Of 838 respondents analyzed, 94% reported cord clamping timing being “very or moderately important” for neonatal outcomes, where midwives more frequently chose “very important” compared to physicians (p < 0.001). Midwives commonly preferred an event-based (e.g., cessation of pulsations) approach to cord clamping. In scenarios involving resuscitation, 27% of midwives and 10% of pediatric physicians, preferred an event-based approach to cord clamping, with a significant difference between groups (p = 0.005). Among obstetricians, 28.8% reported considering an event-based approach to cord clamping in elective cesarean sections. In resuscitation scenarios, obstetricians predominantly selected < 30 s as the preferred timing for cord clamping, whereas pediatric physicians were less likely to do so (p < 0.001). Conclusion Timing of cord clamping is considered important among respondents. The study reveals a generally positive attitude towards delayed cord clamping among health care professionals in Sweden, with notable variations between professional groups. The interprofessional differences highlight the need for shared guidelines and collaborative training to support the potential implementation of intact cord resuscitation.